LINGUISTIC AND TRANSLATION ASPECTS OF POLITICAL CORRECTNESS IN MEDIA TEXTS - Kovalova, Olena; Nikitenko, Olga (Studies in Comparative Education, 2022)
Due to globalisation and forming of international and intercultural relations, the role of political correctness as a guarantor of successful communication between different social groups is growing. Wide use of this lexical layer in media texts, direct influence of politically correct units on social relations through mass media and the insufficient number of studies related to the translation of French politically correct terminology in media discourse determine the relevance of the study. The relevance of the study is due to the factors that there is no single approach to the analysis of political correctness in the scientific literature, and there is no single definition of "political correctness" in spite of the fact that it is firmly established in many languages. Moreover, although political correctness as a tool of communicative strategy of behavior is aimed at avoiding social aggravation and achieving a conflict-free atmosphere in society, provokes a lot of heated debates, which fact does not meet its main purpose and only emphasizes the contradictions. The article is aimed at establishing the means of transmitting the semantic content of politically correct lexical items that function in media texts in the process of their translation. The aim involves solving the following tasks: to systematize theoretical approaches to defining the concept of "political correctness"; establish the structure of the language of political correctness; to determine socio-discursive markers of political correctness in the French media text and on their basis to develop a classification of politically correct units in French mass media; to identify the most optimal means of reproducing the semantic content of French politically correct units in their translation into English .The object of research is social discursive markers of political correctness in the media text. The subject of the research is the means of translating politically correct units in media texts. After the analysis of the media texts, main methods of translating politically correct units were concluded. The translation of French politically correct units is carried out with the help of various translation transformations, the application of which can be complex. Calquing and transcoding are the most common means of reproducing politically correct lexical units in media texts. The frequency of use of these transformations is higher due to the large number of internationalisms that facilitate communication between different cultures.